2005
DOI: 10.1530/rep.1.00269
|View full text |Cite
|
Sign up to set email alerts
|

Role of actin cytoskeleton in mammalian sperm capacitation and the acrosome reaction

Abstract: In order to fertilize, the mammalian spermatozoa should reside in the female reproductive tract for several hours, during which they undergo a series of biochemical modifications collectively called capacitation. Only capacitated sperm can undergo the acrosome reaction after binding to the egg zona pellucida, a process which enables sperm to penetrate into the egg and fertilize it. Polymerization of globular (G)-actin to filamentous (F)-actin occurs during capacitation, depending on protein kinase A activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
173
0
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(190 citation statements)
references
References 47 publications
6
173
0
9
Order By: Relevance
“…2,19,39,49 The cytoskeleton is a highly organized dynamic structure that plays a key role in the shaping and differentiating of spermatids. 50 Two cytoskeletal structures in the seminiferous epithelium, the Sertoli cell apical ES and the spermatid-containing acrosome-acroplaxome-manchette complex, may play cooperative roles in the shaping of the sperm head. 38,39,51 The Sertoli cell apical ES encircles and mechanically grasps the acrosome of the elongating spermatid head with a narrow layer of hexagonally packed, parallel actin bundles.…”
Section: Discussionmentioning
confidence: 99%
“…2,19,39,49 The cytoskeleton is a highly organized dynamic structure that plays a key role in the shaping and differentiating of spermatids. 50 Two cytoskeletal structures in the seminiferous epithelium, the Sertoli cell apical ES and the spermatid-containing acrosome-acroplaxome-manchette complex, may play cooperative roles in the shaping of the sperm head. 38,39,51 The Sertoli cell apical ES encircles and mechanically grasps the acrosome of the elongating spermatid head with a narrow layer of hexagonally packed, parallel actin bundles.…”
Section: Discussionmentioning
confidence: 99%
“…Another important process that occurs during sperm capacitation is actin polymerization; however, at the end of the capacitation, the polymers must disperse to achieve the AR (3). It has been suggested that an increase in F-actin creates a network between the plasma and the outer acrosomal membranes, and the dispersion of F-actin between the two membranes is needed to enable the AR (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Phosphoinositides release gelsolin from actin filament ends, providing sites for actin assembly (14 -17). In vitro studies suggested that gelsolin is phosphorylated by pp60(c-SRC) and that this phosphorylation is enhanced by phosphoinositide 4,5-bisphosphate (PIP 2 (4,5) ) (18) and can interfere with the binding of gelsolin to the actin filaments (19). Previous work identified SRC in human spermatozoa, and it appears to be involved in regulating sperm capacitation, calcium fluxes, tyrosine phosphorylation, and the acrosome reaction (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, two possible roles for PKC in acrosome reaction have been proposed: the first is to trigger a plasma membrane calcium channel to increase intracellular Ca 2+ (Galizzi et al, 1987;Spungin & Breitbart, 1996); the second one is to activate the phospholipase A 2 (PLA 2 ) that generates arachidonic acid (Roldan et al, 1992). Interestingly, a crosstalk between PKA and PKC during sperm capacitation was highlighted by Cohen and colleagues (Cohen et al, 2004;Breitbart et al, 2005) with a consequent rapid increase in actin polymerization which is followed by fast depolymerization, probably because of the increase in Ca 2+ levels. Therefore, spermatozoa ability to fertilize is tightly associated to a remodeling in cytoskeletal compounds.…”
Section: Discussionmentioning
confidence: 99%